Implementasi Green Marketing Pada UMKM Upaya Memasuki Pasar Internasional (Studi Kasus pada Creabrush Indonesia) - Wahdatun Thoibah; Muhammad Arif; Rahmat Daim Harahap (Jurnal Ekonomika Dan Bisnis (JEBS), 2022)
Green Marketing is a marketing activity that pays attention to environmental sustainability. This research was conducted bearing in mind the importance of every business actor to apply Green Marketing in business activities, especially export-oriented ones. One example of a business that implements Green Marketing is the Creabrush UMKM. The purpose of this study is to describe the implementation of Green Marketing in MSME Creabrush as an effort to enter the international market, explain the factors that influence MSME Creabrush management in implementing Green Marketing, to determine the competitive advantage possessed by MSME Creabrush in implementing Green Marketing, as well as the impact of implementation of Green Marketing. This research is a descriptive research with a qualitative approach. The author conducted interviews with the owners and employees of SMEs Creabrush to find out how Green Marketing is implemented in SMEs Creabrush itself. The data analysis technique used is Miles and Huberman's data analysis technique. The results of this study are that the application of Green Marketing to Creabrush SMEs is already environmentally friendly in terms of production, promotion, distribution and pricing activities. Awareness of environmental responsibility, government regulations, competition in similar industries and cost savings in waste management are factors that influence the implementation of Green Marketing in Creabrush SMEs.